2015
DOI: 10.1063/1.4905650
|View full text |Cite
|
Sign up to set email alerts
|

Negative polarity of phenyl-C61 butyric acid methyl ester adjacent to donor macromolecule domains

Abstract: Interfacial fields within organic photovoltaics influence the movement of free charge carriers, including exciton dissociation and recombination. Open circuit voltage (Voc) can also be dependent on the interfacial fields, in the event that they modulate the energy gap between donor HOMO and acceptor LUMO. A rise in the vacuum level of the acceptor will increase the gap and the Voc, which can be beneficial for device efficiency. Here, we measure the interfacial potential differences at donor-acceptor junctions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Computational support for the model was given by Marchiori et al , who concluded for isolated P3HT/C 60 and P3HT/[60]­PCBM-like complexes that an interfacial dipole exists. Several experimental results suggest that a dipolar layer can be formed at donor/acceptor interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational support for the model was given by Marchiori et al , who concluded for isolated P3HT/C 60 and P3HT/[60]­PCBM-like complexes that an interfacial dipole exists. Several experimental results suggest that a dipolar layer can be formed at donor/acceptor interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14] Recently, an experimental study performed by Vandewal et al 8 questions this proposal by revealing that the best materials systems show an internal quantum efficiency higher than 90% without the need for excess electronic or vibrational energy. [20][21][22] suggest that a dipolar layer can be formed at donor/acceptor interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, P3ATs are p-type semiconductors [16][17][18] and have positively charged structures along their chains, these being the radical cations (polarons) and dications (bipolaron) responsible for the transfer of positive charge. Phenyl-C 61 -butyric acid methyl ester (PCBM) can be used as an n-type conductor, as it has the capacity to generate negative polarons and bipolarons, the radical anions and dianions responsible for electron transfer [1,2,[4][5][6][7][8][9][10][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%